Software quality standards - Đorđević, Nebojša D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
In order to achieve the desired software quality, it is necessary to have information about the existing standards in this field and follow them in all phases of the software life cycle. This study emphasizes the importance of applying the standards in the field of software quality. In the last 20 years, the International Organization for Standards has played an important role in the development of quality standards of a number of software products. At the beginning of this work, the evolution of standards in the field of software quality is summarized and then the current series ISO/IEC standard called SQuaRE are described in detail. This area is very important because the knowledge of software quality standards and their application contributes to the development of quality software that will be widely used and durable. The application of the described standards and the evaluation approaches for the quantification of software qualitiy depends on the resources available for carrying out the method (time, money, the number of evaluators and their expertise, the number of users for testing, facilities and test equipment), the required level of objectivity and its application to various stages of the development of applications.
Keywords: ISO; quality standard; software quality